2020
DOI: 10.4103/jfmpc.jfmpc_444_20
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke depression among stroke survivors in Sub-Himalayan region

Abstract: Introduction: Stroke is a leading cause of long-term disability and loss of productive life in developing countries, including India. Ischemic stroke accounts for 85% of all types of stroke with a prevalence of 5%–15% among acute stroke incidents. The prevalence of poststroke depression among acute stroke survivors is varied from 5 to 54%. The study focused on depression among stroke survivors who actively involved in a home-based rehabilitation. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Stroke patients rate themselves as low, feel tired, are physically disabled, and have a low quality of life that will support the occurrence of poststroke depression (Sibbritt et al, 2022). The prevalence of post-stroke depression is higher in patients with reduced mobility, high functional dependence, and more severe functional disabilities (Kumar et al, 2020). In this study, the majority of post-stroke depression was either minimally depressed or not depressed.…”
Section: Nursing Practicesmentioning
confidence: 59%
“…Stroke patients rate themselves as low, feel tired, are physically disabled, and have a low quality of life that will support the occurrence of poststroke depression (Sibbritt et al, 2022). The prevalence of post-stroke depression is higher in patients with reduced mobility, high functional dependence, and more severe functional disabilities (Kumar et al, 2020). In this study, the majority of post-stroke depression was either minimally depressed or not depressed.…”
Section: Nursing Practicesmentioning
confidence: 59%
“…Strokes are the second leading cause of death worldwide and a major cause of disability in adults, impacting not only physical health but also psychological wellness [ 1 ]. A recent study reported that 14% of stroke survivors suffer post-stroke depression [ 2 ]. Subarachnoid hemorrhages (SAHs) are rare, accounting for only 5% of strokes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neurologic and functional deficits, patients also encounter significant challenges in terms of their support system, alteration of self-esteem, change to self-image, and altered living standards [ 3 , 7 ]. Therefore, these patients are prone to development of depressive mood, anxiety, denial behavior, insomnia, or other psychological comorbidities [ 5 , 6 , 8 , 9 ] and have a poststroke depression (PSD) prevalence of 31.1% and a poststroke anxiety prevalence of 20.4% [ 10 , 11 ]. An increased prevalence of emotional disturbance may lead to psychological crisis [ 9 , 12 ], which can be defined as when the summation of stressors faced by an individual exceeds their capacity to cope [ 13 ].…”
Section: Introductionmentioning
confidence: 99%